Classification of Forestry Literature - Ray, M. (Indian Forester, 1999)
Classification of forestry literature has been a thought-provoking topic of research that has been dealt very scientifically by foresters throughout the world as early as in 1003. Several classification schemes have been designed from time to time viz. the Howard System in 1926 (India), Flury System (1933); the Commonwealth Agricultural Bureau (CAB) and the International Union of Forestry Research Organization (lUFRO) and Food & Agriculture Organisation (FAO) of the United Nations have been instrumental in releasing their versions as the Oxford Decimal Classification (ODC) and Forest Decimal Classification (FDC) in 1954 and 1990 respectively. ODC is very elaborate and is perfectly suited for a manual filing and indexing system. This has been revised as the FDC keeping in mind the application of computers in the field information storage and retrieval system.